Foreign Language Reading Anxiety: Exploring First Semester Students' Experiences with Economics English Texts - Himaya Praptani Adys; Himala Praptami Adys (Journal of Innovative and Creativity, 2025)
This investigation examines the phenomenon of foreign language reading anxiety experienced by first-semester Economics Development students at Universitas Negeri Makassar when engaging with specialized English economics texts. The research employed a modified version of Zoghy's Foreign Language Reading Anxiety (FLRA) scale to collect data from 95 respondents, measuring anxiety manifestations across four critical dimensions: text-related anxiety, language-related anxiety, comprehension-related anxiety, and performance-related anxiety. Statistical analysis demonstrated that these Economics Development students encounter moderate to high anxiety levels overall, with particularly elevated anxiety regarding performance evaluation and assessment situations. These findings highlight the necessity for language instructors at Universitas Negeri Makassar to develop and implement strategically targeted interventions addressing reading anxiety, with particular emphasis on alleviating performance-related stress while simultaneously enhancing linguistic competence. The study provides valuable insights into the specific challenges confronted by Economics Development students at Universitas Negeri Makassar as they navigate discipline-specific foreign language materials essential to their academic development.